Smart Parking Dalam Menunjang Implementasi Smart City di Kota Denpasar - Ariesta Agung Permana Putra; I Putu Satwika (Primakara University, 2022)
Density in Denpasar City is increasing every year. In addition to the density of its citizens, vehicles have also increased. This can make it increasingly difficult for Denpasar City to get to Smart City because it cannot achieve Smart mobility which is one of the main points of Smart City itself. One of the scopes of a smart mobility is a parking system. The parking system is one of the scopes of smart mobility because the parking system can be a source of congestion. We can see in several types of events held in Denpasar City, for example, PKB which is an annual event in Denpasar. Many residents of Denpasar City complained that they had difficulty finding parking and ended up looking for other parking alternatives that might be further away. During the search process, most of them will drive their vehicles slowly so that when there is an empty parking lot they don't miss it. The smart parking system is one solution that can be applied to reduce congestion in the city of Denpasar which is increasing. In addition to being able to break down congestion, the Smart Parking system is considered a more efficient system because it uses minimal resources and can use existing human resources as personnel in supervising a parking lot.Smart Parking, Parking Area